VD_FINDINFO Arrêt / 2016 / 201 vom 23. März 2016 - VD Tribunal cantonal (2016)
RECONSIDÉRATION, STATUT DE L'ASSURÉASSURANCE SOCIALE, REVENU SANS INVALIDITÉ | 28a LAI, 4 al. 1 LAI, 16 LPGA, 53 al. 1 LPGA, 53 al. 2 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 8 al. 3 LPGA, 27 RAI, 88bis al. 2 let. a RAI